In search of evidence-based treatment for concussion: characteristics of current clinical trials. (5th November 2014) - Burke, Matthew J.; Fralick, Michael; Nejatbakhsh, Nasrin; Tartaglia, Maria C.; Tator, Charles H.
Abstract: Objective : To assess the characteristics of current clinical trials investigating the treatment of concussion. Background : Recent systematic literature reviews have concluded that there is minimal evidence to support any specific treatment for concussion, including the principles of return-to-activity protocols such as type or duration of rest. Design/methods : Clinical trial data was extracted from Clinicaltrials.gov and seven additional World Health Organization primary registries. The trial databases were accessed up until 3 October 2013. This study used search terms of 'concussion' or 'mild traumatic brain injury' (mTBI) and filtered for interventional trials. Trials that were terminated, already published or not interventional trials of concussion/mTBI were excluded. Results : Of the 142 concussion/mTBI interventional clinical trials identified, 71 met inclusion criteria. Trials had a median estimated enrolment of 60 participants. There was a wide-range of treatments studied, including cognitive/behavioural therapies (28.2%), medications (28.2%), devices (11.3%), dietary supplements (8.5%), return-to-activity/rest (1.4%) and others (22.4%). Heterogeneity among trials for concussion identification/diagnosis and primary outcomes utilized was evident. Symptom-based questionnaires (39.4%) and neuropsychological tests (28.2%) were the most common outcome measures. Conclusions : Diverse, potentially promising therapeutics are currently being studied for the treatment of concussion. However, several deficiencies were identified including a paucity of trials addressing return-to-activity principles. Also, small sample size and trial heterogeneity may threaten scientific evaluation and subsequent clinical application.